RETRACTED: Socio-economic factors in environmental risk management as applied to urban agglomerations - Lisina Natalia; Sedina Natalia; Yatsevich Mariya (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001